Three is a crowd? Some notes about Third Party Funding and its application in commercial arbitrations - Ríos Pizarro, Carlos (2017)
In this article, the author introduces us to the institution of third party funding and its future application in arbitration litigation. Third party funding allows the litigant’s costs can be funded. Moreover, he points out the problems that the third party financing has, and the implementation of rules to deal with this situation. Finally, there is a tendency to expand the duty of disclosure of the parties whether a third party is funding them.